2008
DOI: 10.1002/ijc.23360
|View full text |Cite
|
Sign up to set email alerts
|

COX‐2 and p53 in human sinonasal cancer: COX‐2 expression is associated with adenocarcinoma histology and wood‐dust exposure

Abstract: The causal role of wood‐dust exposure in sinonasal cancer (SNC) has been established in epidemiological studies, but the mechanisms of SNC carcinogenesis are still largely unknown. Increased amounts of COX‐2 are found in both premalignant and malignant tissues, and experimental evidence link COX‐2 to development of cancer. Many signals that activate COX‐2 also induce tumor suppressor p53, a transcription factor central in cellular stress response. We investigated COX‐2 and p53 expressions by immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…In addition, we confirmed a tendency of higher p53 positivity in the samples from patients with wood etiology, but not in the number of samples with some p53 positivity. Studying both ITAC and sinonasal squamous carcinoma, Holmila and coworkers also noted a trend for higher p53 expression in wood dust-related patients [19]. We found no difference in p53 expression between smokers and nonsmokers, and this was also seen by Holmila et al [19].…”
Section: Resultssupporting
confidence: 85%
“…In addition, we confirmed a tendency of higher p53 positivity in the samples from patients with wood etiology, but not in the number of samples with some p53 positivity. Studying both ITAC and sinonasal squamous carcinoma, Holmila and coworkers also noted a trend for higher p53 expression in wood dust-related patients [19]. We found no difference in p53 expression between smokers and nonsmokers, and this was also seen by Holmila et al [19].…”
Section: Resultssupporting
confidence: 85%
“…2,52 In our recent study on a subset of the current sinonasal cancers, cyclooxygenase-2 protein, an enzyme associated with inflammation and DNA damage, and known to interact with p53, was shown to be highly expressed in adenocarcinomas in association to wood-dust exposure. 53 In summary, our current molecular epidemiology study demonstrates a high load of TP53 mutations in human sinonasal cancer, with the occurrence of TP53 mutation significantly increased in association to long duration and high level of exposure to wood dust. Smoking was not observed to influence the overall risk of having a TP53 mutation, but was associated with multiple TP53 mutations.…”
Section: Discussionmentioning
confidence: 69%
“…13,14 Until the present moment, genetic studies on sinonasal SCCs have demonstrated TP53 mutations and p53 overexpression in up to 56% of cases. [15][16][17] Kras mutations have been reported, but only in 1% of cases. 18 Bandoh et al 16 suggested that TP53 mutations and a low apoptotic index are associated with poor survival.…”
mentioning
confidence: 96%
“…Cyclooxygenase 2 (COX2) expression was observed in low frequency, which may rule out a possible role for chronic inflammation in sinonasal SCC development. 17 Using loss of heterozygosity analysis, Götte et al 19 have shown losses on chromosomes 3p, 8p, 17p, and 18q. There are very few genome-wide studies on genetic changes in sinonasal SCC.…”
mentioning
confidence: 98%